The Representation of ICT Competencies in English Language Reading Skill Modules for Open University - Jody Furqon Sanjaya; Sri Sumarni (Stairs, 2020)
The current global and national issues require students to upgrade their level of ICT competencies in this 21st century. To meet the new standard, there is a need to upgrade the development of the learning materials. Therefore, this study is aimed to portray the ICT competencies covered in the reading skill modules as a concern in addressing the issue of ICT competencies development in education. The qualitative content analysis is used as the method of this study. The main source of data is reading skills modules which are taken from four reading courses (Reading I, II, III, and IV) in Open University English Education Study Program. The results of this study show that 90 representations of ICT competencies are found and mostly represented in the form of Hypermedia, followed by Hyperlink, Multimedia (graphs, tables, and diagrams) and Communication Media (e-mail). The analysis of the table of ISTE NETS (2016) shows that Knowledge Constructor is the most dominant standard (74%), followed by Computational Thinker (16%), and Creative Communicator (10%).